2019
DOI: 10.3390/polym11061018
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Composites with Silver (I) Cyanoximates Inhibit Biofilm Formation of Gram-Positive and Gram-Negative Bacteria

Abstract: Biofilms are surface-associated microbial communities known for their increased resistance to antimicrobials and host factors. This resistance introduces a critical clinical challenge, particularly in cases associated with implants increasing the predisposition for bacterial infections. Preventing such infections requires the development of novel antimicrobials or compounds that enhance bactericidal effect of currently available antibiotics. We have synthesized and characterized twelve novel silver(I) cyanoxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…During the past decade, there has been an increasing awareness that S. aureus biofilms are a major cause for concern in multiple infections 6 . As reported by the National Institutes of Health (NIH), over 60% of all bacterial and 80% of chronic bacterial infections are associated with biofilm formation 7 . Meanwhile, infections caused by biofilm formation of S. aureus are hard to treat 8 .…”
Section: Introductionmentioning
confidence: 99%
“…During the past decade, there has been an increasing awareness that S. aureus biofilms are a major cause for concern in multiple infections 6 . As reported by the National Institutes of Health (NIH), over 60% of all bacterial and 80% of chronic bacterial infections are associated with biofilm formation 7 . Meanwhile, infections caused by biofilm formation of S. aureus are hard to treat 8 .…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of the medical device and food packaging surfaces with pathogenic bacteria might lead to the biofilm formation, thereby it can cause serious acute and chronic infections to people [ 8 , 9 ]. Biofilm composed of multi-species are difficult to remove through host defense systems or by the antibiotic treatment [ 5 , 6 , 10 ]. Therefore, recently it has become imperative to advance various treatment approaches for biofilm eradication.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the differences in the structure between Gram-positive and Gram-negative cell walls and showed different modes of action of the tested compounds. 36 The tested compounds showed 14.38% (4e) to 37 Altogether, our study demonstrated that the compounds inhibit biofilm formation and had the potential for anti-biofilm activity. The disc diffusion method was used to enumerate the antibacterial activities of the synthesized compounds; no zones of inhibition were observed around the discs impregnated with chemical compounds (Figure S1).…”
Section: 34mentioning
confidence: 58%